Paclitaxel Coated Balloon vs. Bare Metal Stent for Endovascular Treatment of Symptomatic Vertebral Artery Origin Stenosis Patients: Protocol for a Randomized Controlled Trial - Wang, Yabing; Ma, Yan; Gao, Peng; Chen, Yanfei; Yang, Bin; Feng, Yao; Jiao, Liqun (Frontiers in Neurology, 2021)
Background: Stenting treatment for refractory symptomatic patients with vertebral artery origin stenosis (VAOS) is safe; however, there is a high rate of in-stent restenosis. Although drug-eluting stents can reduce the incidence of restenosis to some extent, there is still a risk caused by stent fracture. Drug-coated balloon (DCB) has been proven to reduce the rate of restenosis in peripheral and coronary artery disease. DCB can prevent inflammation caused by extraneous material stimulation and allow the subsequent treatment that is characteristic of “leave nothing behind”. The purpose of this trial is to compare the efficacy and safety of DCB and bare metal stent (BMS) in the treatment of VAOS. Method/design: This trial is a 1:1 randomized, controlled, multicenter, non-inferiority trial that compares the DCB to BMS in terms of angiographically assessed target lesion binary restenosis (≥50%) at 12 months in endovascular treatment of symptomatic patients with VAOS. Discussion: A total of 180 patients with symptomatic VAOS who match the trial eligibility criteria will be randomized 1:1 to treatment with DCB (n=90) or BMS (n=90). An angiographic core laboratory-adjudicated target lesion binary restenosis (≥50%) at 12 months of follow-up was selected as primary efficacy endpoint to assess the DCB treatment effect. A clinical events committee will assess the safety endpoints of all-cause death, target vessel related transient ischemic attack and ischemic or hemorrhagic stroke events. A data safety monitoring board will periodically review safety data for subject safety, the study conduct, and progress. In this trial, randomization is only allowed after successful pre-dilatation. We anticipate that this trial will provide rigorous data to clarify whether DCBs are beneficial in patients with symptomatic VAOS. Trial registration: NCT03910166